2000
DOI: 10.30843/nzpp.2000.53.3631
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of apple leafcurling midge (<i>Dasineura mali</i>) and its parasitoid (<i>Platygaster demades</i>)

Abstract: Apple leafcurling midge (Dasineura mali) (ALCM) can seriously damage apple tree leaves. Insecticides may be applied to the soil in spring to kill ALCM emerging from overwintering sites. ALCM emergence was studied in the Waikato, Hawke's Bay, Nelson, Canterbury and Central Otago over two seasons (1998/99 and 1999/ 2000) using cages placed over the soil beneath apple trees. ALCM and its egg parasitoid (Platygaster demades) emerged over a similar period of time. Emergence in southern districts began later and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
0
12
0
2
Order By: Relevance
“…1). Close synchrony of fi rst generation midge and parasitoid adults, both emerging from over-wintering populations, has been reported by Tomkins et al (2000). The mechanism that leads to the synchrony of emergence of the fi rst generations is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Close synchrony of fi rst generation midge and parasitoid adults, both emerging from over-wintering populations, has been reported by Tomkins et al (2000). The mechanism that leads to the synchrony of emergence of the fi rst generations is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Numbers of P. demades were not monitored in 1996-97, but were estimated by averaging trap catch data from three sites over three seasons (2001 to 2004) and offsetting this against ALCM phenology in 1996-97 so that the fi rst generation P. demades peak matched that of its host, as is observed in the fi eld (Todd 1959;Tomkins et al 2000) ( Fig. 1).…”
Section: Methods Alcm and P Demades Monitoringmentioning
confidence: 99%
“…A second series of 16 traps in four replicate 1 ha plots were deployed from 24-27 August to 25 October 2007 (first generation) and from 11 December 2007 to 19 February 2008 (third generation). 29 These traps (33 m spacing) were designed to produce the corner/centre ratio and edge/centre ratio as above. Traps were operated over the first and much larger third generations in order to determine the reproducibility of the results, in case there was an effect of insect density.…”
Section: Apple Leaf Curling Midge Dasineura Mali (Diptera: Cecidomyiimentioning
confidence: 99%
“…data) show that these two species have four generations a year in Palmerston North, with the oviposition by adults of each generation occurring as follows: overwintered generation, late September-late October; first generation, late November-early January; second generation, mid January-early March; and third generation, early March-early April. Tomkins et al (2000) reported the emergence of overwintered populations of ALCM and P. demades in spring. More recently, Sandanayaka & Charles (2006a) investigated the effect of temperature and diet on adult longevity of P. demades.…”
Section: Introductionmentioning
confidence: 99%